The Sosialisasi pencegahan narkoba untuk menumbuhkan kesadaran, mencegah bahaya dan merawat masa depan bangsa: Drug Prevention Socialization to Cultivate Awareness, Mitigate Risks, and Nourish the Nation's Future - Irayanti, Irma; Sundawa, Dadang; Sakban, Abdul; Solihin, Ely; Albab, M. Bikki Ulil; Rindiana, Rani Irmawati; Nuraeni, Wulan; Lukitosari, Zhafira Oktafiani (Sam Ratulangi University, 2024)
Statistical data indicates an increase in drug abuse cases worldwide, including in Indonesia. Drug abuse has become a serious problem affecting various segments of society, including urban students in Bandung. This is a serious concern as it impacts the health and behavior of students who represent the nation's future. Addressing this issue requires effective preventive measures to reduce drug abuse among students through drug abuse prevention socialization. The objective of this activity is to provide new knowledge to high school students about drugs and the importance of legal education in drug abuse. The implementation method involves collaboration with the National Narcotics Agency (BNN) of West Java, involving 503 students with speakers from BNN of West Java. Evaluation is conducted to measure the success rate of the activity. The results show that this socialization activity has a positive impact, increasing awareness and knowledge among students about the dangers of drug abuse. Collaboration between BNN, educational institutions, and the community in drug education socialization programs is considered effective in preventing drug abuse among students. This article contributes by presenting survey results and drug abuse prevention instruments among students to prevent drug abuse, cultivate awareness, mitigate risks, and nurture students as the nation's future. ABSTRAK Data statistik menunjukkan peningkatan kasus penyalahgunaan narkoba di berbagai negara, termasukIndonesia. Penyalahgunaan narkoba menjadi masalah serius yang mempengaruhi berbagai kalangan,termasuk pelajar kota Bandung. Hal ini menjadi perhatian serius karena berdampak terhadap kesehatan danperilaku pelajar yang menjadi masa depan bangsa. Masalah ini memerlukan tindakan pencegahan yangefektif untuk mengurangi penyalahgunaan narkoba di kalangan pelajar melalui sosialisasi pencegahanpenyalahgunaan narkoba. Tujuan kegiatan ini adalah untuk memberikan pengetahuan baru bagi pelajarSMA tentang narkoba dan pentingnya pendidikan hukum dalam penyalahgunaan narkoba. Metodepelaksanaan dilakukan dengan kerjasama Badan Narkotika Nasional (BNN) Jawa Barat, melibatkan 503siswa dengan narasumber dari BNN Provinsi jawa Barat. Evaluasi dilakukan untuk mengukur tingkatkeberhasilan kegiatan. Hasilnya menunjukkan bahwa kegiatan sosialisasi ini memberikan dampak positif,meningkatkan kesadaran dan pengetahuan siswa tentang bahaya penyalahgunaan narkoba. Kerjasamaantara BNN, lembaga pendidikan, dan masyarakat dalam program sosialisasi penyuluhan narkoba dianggapefektif dalam mencegah penyalahgunaan narkoba di kalangan pelajar. Artikel ini memberikan kontribusidalam menyajikan hasil survei dan instrumen pencegahan penyalahgunaan narkoba di kalangan pelajaruntuk mencegah penyalahgunaan narkoba, menumbuhkan kesadaran, mencegah bahaya dan merawatpelajar sebagai masa depan bangsa.